A Study on Intelligent Manufacturing Industrial Internet for Injection Molding Industry Based on Digital Twin. (13th January 2021) - Wang, Zhiyong; Feng, Wei; Ye, Junlin; Yang, Jinbiao; Liu, Chun
Abstract : As one of the basic manufacturing industries in China, injection molding industry is faced with the problems of low degree of informatization and intelligence, resulting in low production efficiency and high costs. It is urgent to integrate deeply with new generation of information technology to achieve transformation and upgrade. In this paper, an integrative industrial Internet architecture of "integration of intelligent equipment, intelligent production lines, intelligent workshops, intelligent factories, and intelligent formats" was described. The injection molding intelligent control system, the production management, control platform based on the MES system, and other key technologies were researched. Also, the smart factory architecture based on digital twin was established, and the implementation method of the smart factory digital twin system was elaborated. The feasibility and effectiveness of the method had been verified through the industrial application, which provided the technical supports for the injection molding industrial Internet system. Finally, the intelligent manufacturing industrial Internet cloud platform for injection molding industry was prospected.